PERANCANGAN HEROINE GAME DATING SIMS “PARAS” - Bima Bahari, Dini Faisal, S.Ds., M.Ds., San Ahdi, S.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Dating sims Game PARAS is a simulation game with interaction pattern of a relationship which is inside the gameplay there are various content is close to indonesian. One of which is design of the heroine. Heroine is a the main woman character in dating sims games. The goals is to make the significant diferent with a dating sims games in japan and hopefully to make a teenagers in indonesia more close to content in indonesia.Method use in design of the heroine is a brainstorming method and after that is observation, quesioner and interview. The result of the data colecting is the fondation to design the heroine in dating sims game PARAS.Keywords : Game, Dating Sims, PARAS, Heroine